Tissue localization of beta receptors for platelet-derived growth factor and platelet-derived growth factor B chain during wound repair in humans. - Reuterdahl, C (1993)
The expression and localization of PDGF beta receptors and PDGF-AB/BB in human healing wounds was evaluated by immunohistochemical techniques and in situ hybridization. Expression of PDGF beta receptor protein and PDGF-AB/BB were analyzed in wound margin biopsies using the PDGFR-B2 and PDGF 007 antibodies. PDGF beta receptor expression was minor in normal skin. An increased expression of PDGF beta receptor protein was prominent in vessels in the proliferating tissue zone in wounds as early as 1 d after surgery and was apparent < or = 4 wk after surgery. There was also a concordant increase in PDGF beta receptor mRNA detected by in situ hybridization. PDGF-AB/BB was present in healing wounds as well as in normal skin. In normal skin, expression of PDGF-AB/BB was confined to peripheral nerve fibers and to solitary cells of the epidermis and of the superficial dermis. In wounds, infiltrating mononuclear cells also stained for PDGF-AB/BB. To identify cell types expressing PDGF AB/BB and PDGF beta receptors, respectively, we performed double immunofluorescence stainings. PDGF beta receptors were expressed by vascular smooth muscle cells and cells in capillary walls; the receptor protein could not be detected in neurofilament containing structures, T lymphocytes, or CD68 expressing macrophages. PDGF-AB/BB colocalized with neurofilaments, it was present in Langerhans cells of the epidermis and in HLA-DR positive cells located in the epidermal/dermal junction area. Of the macrophages infiltrating the wound, 43 +/- 18% stained positively for PDGF AB/BB. Since PDGF-AB/BB and PDGF beta receptors are expressed in the healing wound, two essential prerequisites for a role of PDGF in wound healing are fulfilled.